How to define the adult in 2020? - Maria Herzog (International Journal of Business and Social Science Research, 2020)
Abstract Today adulthood seems to be characterized also by a certain number of obligations and the assumption of responsibilities. It is an age in which the life course in the form of an institutional processing program seems to be undermined. This can be seen in the extended periods of schooling, teaching, training and the associated shortening of the working phase of a lifetime. Adulthood is to be understood as a social construct resulting from current demands and ideas. A diverse multidisciplinary presentation of the demands placed on adults will be discussed and a holistic representation of the concept of the adult will be developed. Which educational, biological, philosophical, legal, economic and psychological approaches and theories are relevant here? In view of this, adulthood can currently be defined on the basis of various interdisciplinary characteristics. Adulthood is defined as a phase that is open to development and begins with (sexual) maturity. The adult moves between dependence and autonomy, striving for autonomy. The adult is also characterized by responsibility and "wisdom". Adulthood is therefore to be understood from the perspective of contemporary educational science as a phase of development in which the relationship of the individual to himself and his environment changes through the mastering of age-related demands and the examination of the social and material environment. The adult thereby experiences himself/herself as a legally mature being who assumes economic and social responsibility for him/herself.